PENGARUH MODERNISASI ADMINISTRASI BERBASIS E-SAMSAT, KUALITAS PELAYANAN DAN SANKSI PAJAK TERHADAP KEPATUHAN PERPAJAKAN KENDARAAN BERMOTOR DI KABUPATEN BOYOLALI - Trivina Damayanti; Desy Nur Pratiwi; Darmanto Darmanto (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the influence of e-Samsat-based administrative modernization, service quality, and tax sanctions on motor vehicle tax compliance in Boyolali Regency. The background of this research is based on the importance of motor vehicle tax revenue as a source of regional income, as well as the challenges in improving taxpayer compliance amidst technological advancements and public service developments. The research method used is quantitative, with data collected through questionnaires distributed to motor vehicle taxpayers. The analysis results show that administrative modernization through e-Samsat, improved service quality, and the implementation of tax sanctions have a significant positive effect on motor vehicle tax compliance. These findings indicate that efforts to digitize services and enhance public service quality, combined with strict enforcement of sanctions, can increase taxpayer compliance in Boyolali Regency.